Pengaruh Persepsi terhadap Intensitas Penggunaan Media Sosial terhadap Prestasi Belajar Akidah Akhlak di MAN 4 Ngawi: The Influence of Perception on Social Media Usage Intensity on Akidah Akhlak Learning Achievement at MAN 4 Ngawi - Muwahidah Nurhasanah; Raharjo (Educan, 2024)
This study aims to analyze the impact of perceptions regarding the intensity of social media usage on performance in the fields of Aqidah (faith) and Akhlak (ethics). The research method employed is a survey using questionnaires distributed to respondents who are active social media users. Data were collected and analyzed using the Pearson product-moment correlation to measure the relationship between social media usage and academic performance in Aqidah and Akhlak. The results indicate a significant effect of perceptions about social media usage intensity on Aqidah and Akhlak's performance. Specifically, it was found that a higher intensity of social media use correlates with better performance in Aqidah and Akhlak. Factors such as usage duration, types of content consumed, and online social interactions also significantly impact Aqidah and Akhlak's performances. The study was conducted at MAN 4 Ngawi, where the COVID-19 pandemic led to the adoption of social media for learning activities, including platforms such as WhatsApp, Google Classroom, and e-learning. The findings emphasize the importance of awareness and prudent management of social media use in efforts to enhance performance in Aqidah and Akhlak. The implications of this research can offer insights for individuals, families, and communities to consider and manage social media usage patterns for better character development and higher achievement in spiritual and moral aspects.